Intercultural Approaches to the Cultural Contento of Indonesia ELT Textbooks: A Library Research - Linda Budiarsih; Yohanes Gatot Sutapa Yuliana; Clarry Sada (IKIP PGRI Pontianak, 2023)
The purpose of this study is to describe the cultural content of some Indonesian ELT Textbooks based on the intercultural approaches. Intercultural approaches in English Language Teaching may increase the awareness on three things, they are native culture, target culture, and international culture. The data were collected based on three journals that have been written by some Indonesian researchers in the same field of research. They are: Muhammad Iwan Munandar and Imaratul Ulwiyah (2012), Gisela Elshadelin and Mateus Yumarnamto (2020), and Deswila, et al (2021). The method of this study is descriptive qualitative method by using systematic literature review. The journals were taken from Research Gate site and Google Scholar search engine. The findings are presented descriptively by discussing (1) the ELT textbooks that become the sample, (2) the aspects of culture content in each article that can be found in ELT Textbook, (3) and the implication of the cultural representation in each textbook. It is hoped that the discussion from the three journal articles will be helpful for the ELT teachers to get the knowledge about cultural content in each textbook and be more creative to enhance the students’ intercultural competence while learning English as the second language.